Influence of potential liquid desiccants on solution cooling, heating, and pumping loads of membrane-based liquid desiccant air conditioning system: An analytical study. (3rd July 2019) - Kumar Reddy, Y. Siva; Balasubramanian, Karthik; Chandramohan, V.P.
Abstract : This paper is intended to study the methodology for choosing the suitable desiccant solution among LiCl, CaCl2, LiBr, and KCOOH solutions (commonly used potential solutions) at optimum heat capacity for an energy-efficient membrane-based liquid desiccant air conditioning system. An analytical model which is validated with existing experimental and numerical results was adopted in this study to find the output parameters. Performance indices considered in this study are solution pumping power, solution heat addition rate (Qadd ), and chiller load (Qchiller ). Considering the specified solutions at their maximum safe concentrations (0.40, 0.35, 0.55, and 0.75, which are just below their saturation concentrations), performance indices analyzed at fixed ambient condition and dehumidification rate at different heat capacity ratios (Cr * = 4.0, 3.0, 2.5, 2.0, and 1.5). At their corresponding optimum Cr *, Qadd is observed low for CaCl2, whereas it was high for LiBr. Solution pumping power and Qchiller are observed as lesser for the LiBr solution. At their corresponding design parameters, LiBr solution's investment cost is found to be 30% higher than LiCl solution's, but its operating cost (pumping power) is nearly 26% to 40% less than the LiCl solution, which suggests that the LiBr solution is the most efficient solution among the four.